Studies in Tuluva history and culture, from the pre-historic times upto the modern - Gururaja Bhatt, P., 1924-1978 (Gururaja Bhatt, 1975)
History and culture of Tulu Nadu, Tulu speaking region comprising the present South Kanara District and the coastal belt of North Kanara District in Karnataka.